Collaboration between teachers and parents of children with ASD on issues of education. (August 2016) - Syriopoulou-Delli, Christine K.; Cassimos, Dimitrios C.; Polychronopoulou, Stavroula A.
Highlights: ⿢ The study examines the views of teachers and parents on critical issues concerning their collaboration in the education of children with ASD. ⿢ The majority of teachers and parents were found to be of the opinion that communication and collaboration between teachers and parents are rendered as critical. ⿢ Postgraduate academic studies and working experience with children with ASD are seen to be the most important factors shaping the attitudes of teachers towards collaboration with parents. Abstract: This study examines the views of teachers and parents on critical issues concerning their collaboration in the education of children with ASD. For the purposes of this study, a total of 171 teachers and 50 parents of children with ASD, attending mainstream or special primary school units, were randomly selected in Greece in order to respond to a structured questionnaire. The majority of teachers and parents were found to be of the opinion that communication and collaboration between teachers and parents are rendered as critical [n = 165 teachers (96.5%), n = 50 parents (100%)]. Postgraduate academic studies and working experience with children with ASD are seen to be the most important factors shaping the attitudes of teachers towards collaboration with parents. On the other hand, the types of working unit teachers were employed in are seen to rank in lower importance.